Honouring Darkness: A documentary film about the psychological struggle towards wholeness - Juan Camilo Roman Estrada 1978- (2019)
This report is about my final project for my master’s degree in Cultural Media Communication (HMM) at the University of Iceland. As a final project I chose to make a documentary film about the aim of becoming a wholesome individual, through the help of certain practices, such as “facing the shadow” and meditation. This quest is narrated by a remarkable person, a doctor, psychiatrist and practitioner of the tantric tradition of Sri Vidya. In the report I explain the making of the documentary, from being an initial idea to becoming a final product. I discuss the possibility of using cinematographic language for communicating abstract ideas and knowledge. I also try to position my work within the framework of film and documentaries. Finally, I put forward a short analysis of the main concepts that are brought up in the documentary. Greinargerð þessi fjallar um lokaverkefnið mitt í meistaranámi í hagnýtri menningarmiðlun við Háskóla Íslands. Lokaverkefnið mitt er heimildamynd sem fjallar um það markmið að verða heilstæðari einstaklingur með því að iðka ákveðnar æfingar, svo sem að standa andspænis skugganum og stunda hugleiðslu. Í heimildamyndinni segir einn maður, læknir, geðlæknir og iðkandi tantrískrar hefðar Sri Vidya, frá þessari leit. Í greinargerðinni er fjallað um gerð heimildamyndarinnar, allt frá hugmynd til lokaafurðar. Fjallað er um möguleika kvikmyndagerðar til að miðla flóknum hugmyndum og þekkingu. Þá er reynt að finna heimildamyndinni stað í fræðilegum kenningum um kvik- og heimildamyndir. Að lokum er sett fram stutt fræðileg umfjöllun um þau hugtök sem saga heimildamyndarinnar hverfist um.